The Glial Cells Respond to Spinal Cord Injury - Wang, Ruideng; Zhou, Rubing; Chen, Zhengyang; Gao, Shan; Zhou, Fang (Frontiers in Neurology, 2022)
It is been over 100 years since glial cells were discovered by Virchow. Since then, a great deal of research was carried out to specify these further roles and properties of glial cells in central nervous system (CNS). As it is well-known that glial cells, such as astrocytes, microglia, oligodendrocytes (OLs), and oligodendrocyte progenitor cells (OPCs) play an important role in supporting and enabling the effective nervous system function in CNS. After spinal cord injury (SCI), these glial cells play different roles in SCI and repair. In this review, we will discuss in detail about the role of glial cells in the healthy CNS and how they respond to SCI.